Development of microbial fuel cell as biosensor for detection of organic matter of wastewater - Sumaraj, Sumaraj; M, Ghangrekar M (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The removal of biodegradable organic matters (BOM) is a very important aspect of evaluating the treatment efficiency in a wastewater treatment plant. However, conventional Biochemical Oxygen Demand (BOD) method is time consuming (3 or 5 days) and not suitable for online process monitoring. Instead biosensors can be used to measure BOD. Microbial Fuel Cell (MFC) biosensor which uses electroactive biofilms as sensing element has the advantage of long-term stability and minimizes the replacement of sensing elements. BOM could be directly converted to electricity via MFC, where MFC itself is an integration of signal generator and transducer. Proton Exchange Membrane (PEM) is a very important component of MFC and the most widely used Nafion PEM (NPEM) is costly (Jurado and Colomer, 2002; Liu et al., 2006, Jana et al., 2010). Previously, researchers have successfully used low cost clayware separators as PEM (CWPEM) with improved performance of MFC (Behera et al., 2009, Jana et al., 2010). Comparative studies has been carried out between MFC-1 (NPEM) and MFC-2 (CWPEM) to evaluate the performance of MFC as biosensor using mixed anaerobic culture with synthetic wastewater containing acetate as source of carbon. MFC-1 biosensor responds linearly between COD (Chemical Oxygen Demand) concentration of 22 mg/L and 51 mg/L (R2=0.954) with a response time between 120 min and 210 min. Similarly, MFC-2 biosensor responds linearly between a concentration 64 mg/L and 212 mg/L (R2=0.949) with a response time between 310 min and 120 min. The variation in rate of proton conductivity (PC) and thickness of the separators is suspected to be the cause for variation in range of detection and response time. The current market price of NPEM is very high i.e. Rs. 4000/10 cm2 and that of CWPEM is Rs. 4/10 cm2. With improvement in PC of CWPEM, low cost MFC biosensor can be successfully developed. Once successfully developed, such low cost MFC based sensors can be calibrated for BOD. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>